Scoring variables and judge bias in United States dressage competitions - Diaz, A. E.; Johnston, M. S.; Lucitti, J.; Neckameyer, W. S.; Moran, K. M. (Journal of Quantitative Analysis in Sports, 2010)
Dressage is an Olympic equestrian discipline with rules governed by The Fédération Equestre Internationale (FEI). After questions arose regarding dressage scoring during the 2008 Olympics, the FEI undertook studies of dressage scoring at international equestrian competitions in Europe. These studies included investigations of scoring scales and judging bias. Based on those results, the FEI recommended the use of statistics to improve the consistency of judge training in dressage competition. The authors performed a statistical analysis of dressage scores earned by riders in the United States. This work demonstrates the lack of consistency in judging in the United States. This is the first published study that looks at U.S. dressage results. It includes a very large data set considered representative of the population of riders in the U.S. Dressage is a subjectively judged sport. The final score, not the class placing, is of greatest importance when assessing rider results. The authors show how mainstream statistical tools can identify factors impacting the final dressage score. Analysis of Variance (ANOVA) was used to demonstrate the existence of key variables which impact scores. The analysis shows there are variations in scoring patterns by horse breed, as well as the existence of high-scoring and low-scoring judges. Finally, the analysis shows that there are increased standard deviations at the "extremes" of the judging scale. This would indicate there is variability in interpretation of scoring at the upper and lower ends of the scoring scale. Analysis of Means (ANOM) identified five judges whose scores were statistically different than the grand average scores.